Swelling characterization and drug delivery kinetics of polyacrylamide-co-itaconic acid/chitosan hydrogels (eXPRESS Polymer Letters)
Hybrid polymeric networks composed of polyacrylamide and chitosan were developed to determine their swelling and ascorbic acid delivery kinetics at various chitosan concentrations. The hybrid acrylamide/chitosan hydrogels were synthesized in aqueous itaconic acid solution (1% w/w). Young’s modulus was also evaluated for the hydrogels, and the results were correlated with the swelling properties. Swelling experiments were carried out using three different pH solutions: acidic (pH 4 buffer solution), neutral (distilled water) and basic (pH 10 buffer solution). The results of the swelling study showed that the swelling properties of the network varied with the changes of the pH in the swelling solution, as well as concentration of chitosan. When chitosan concentration increased, the swelling capacity diminished, and therefore Young’s modulus increased. The results indicated that the swelling process followed a second order kinetics. The ascorbic acid diffusion inside the hydrogel follows a Fickian mechanism. The ascorbic acid diffusion coefficients are reported as a function of chitosan concentration.